Emergence of extensive drug-resistant (XDR) Acinetobacter baumanniiin the Clinical Center University of Sarajevo, Bosnia and Herzegovina - Amela Dedeić-Ljubović; Đana Granov; Mirsada Hukić (Medicinski glasnik, 2015)
Aim: Recently increased attention and interest for Acinetobacterbaumanniiare the result of the occurrence of multidrug resistant (MDR), extensive drug resistant (XDR) and pandrug resistant (PDR) isolates around the world. The aim of this study was to examine the resistance of A. baumannii isolates to antimicrobials in Clinical Centre University of Sarajevo, Bosnia and Herzegovina. Methods: Two hundred and fifty-seven A.baumannii isolates were collected between July 2011 and June 2012 in different wards and from different clinical samples.Multidrug resistant, XDR and PDR were defined according to international expert proposal for interim standard definitions for acquired resistance. Results: A total of 257A. baumannii isolates showed eleven different patterns of resistance,of which ten patterns corresponded to MDR and one corresponded to XDR (sensitive only to colistin). Multidrug resistant and XDR strains were the most common at Intensive Care Units andsurgical departments. The largest numbers of isolates were found in wound swabs, blood and bronchial aspirate. Conclusion: This is the first report of XDR A. baumannii in the 2000-bed Clinical Centre University of Sarajevo, Bosnia-Herzegovina. Although XDR strains have been detected,the resistance to colistinhasnot. The elevated prevalence of these strains indicates that local antibiotic prescription policies should be revised and infection prevention and control should be improved.
Keywords: antimicrobials; nosocomial infections; intensive care unit